2023
DOI: 10.51248/.v43i01.2082
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical variables as a predictor marker in type 2 diabetes mellitus and diabetic complications

Abstract: Introduction and Aim: Various biochemical and hematological variables are important for predicting the progression of diabetes to diabetic complications, analyzing health-economic status, and examining the effectiveness of antidiabetic agents. The aim of this study is to find the association between clinical variables and type 2 diabetes, diabetic nephropathy and cardiovascular disease.   Materials and Methods: A total of 300 participants’ details were studied and divided into 3 groups; type 2 diabetes (n=100)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This may be because the SII values of all patients already diagnosed with DR were higher than the SII of only patients with Type 2 DM due to inflammation. In a study in which 100 uncomplicated Type 2 DM patients were included, and many biomarkers were examined, the mean SII value was found to be 470.91 [28]. In our study, all of our patients were Type 2 DM patients with DR diagnosis, and the mean value for SII was found to be 821.4.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This may be because the SII values of all patients already diagnosed with DR were higher than the SII of only patients with Type 2 DM due to inflammation. In a study in which 100 uncomplicated Type 2 DM patients were included, and many biomarkers were examined, the mean SII value was found to be 470.91 [28]. In our study, all of our patients were Type 2 DM patients with DR diagnosis, and the mean value for SII was found to be 821.4.…”
Section: Discussionmentioning
confidence: 47%
“…Because we do not know how many of these deceased patients had DR progression. In a study of 300 Type 2 DM patients on whether SII has a predictive value for diabetic nephropathy and cardiovascular diseases in patients with Type 2 DM, predictive SII values were found for cardiovascular diseases and diabetic nephropathy [28]. In a study investigating the relationship between SII and diabetic neuropathy in 1460 hospitalized type 2 DM patients in China, it was found that SII levels were significantly higher in patients with diabetic neuropathy [29].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the SII values of all patients already diagnosed with DR were higher than the SII of only patients with type 2 DM due to inflammation. In a study in which 100 uncomplicated type 2 DM patients were included, and many biomarkers were examined, the mean SII value was found to be 470.91 [ 31 ]. In our study, all of our patients were type 2 DM patients with DR diagnosis, and the mean value for SII was found to be 821.4.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we do not know how many of these deceased patients had DR progression. In a study of 300 type 2 DM patients on whether SII has a predictive value for diabetic nephropathy and cardiovascular diseases in patients with type 2 DM, predictive SII values were found for cardiovascular diseases and diabetic nephropathy [ 31 ]. In a study investigating the relationship between SII and diabetic neuropathy in 1460 hospitalized type 2 DM patients in China, it was found that SII levels were significantly higher in patients with diabetic neuropathy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that these changes may affect the red blood cells (RBCs), white blood cells (WBCs), platelets, and their coagulatory factors (Noori et al, 2022). It's interesting to observe that diabetes patients' differential WBC counts increased overall despite no change in the proportion of monocytes, including basophils, eosinophils, and neutrophils (Suvarna et al, 2023). Studies have shown that increased platelet reactivation in diabetic patients will likely result in less cardiovascular protection (Mainoli et al, 2021) because many studies have shown that hyperinsulinemia and insulin resistance are directly linked to erythroid progenitors' stimulation, leading to increased pro-inflammatory markers that predispose patients to diabetic complications (Ellinger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%